2016
DOI: 10.1038/mi.2015.113
|View full text |Cite
|
Sign up to set email alerts
|

miR-511-3p, embedded in the macrophage mannose receptor gene, contributes to intestinal inflammation

Abstract: MiR-511-3p is embedded in intron 5 of the CD206/MRC1 gene Mrc1, expressed by macrophage and dendritic cell populations. CD206 and miR-511-3p expression are co-regulated, and their contribution to intestinal inflammation is unclear. We investigated their roles in intestinal inflammation in both mouse and human systems. Colons of CD206-deficient mice displayed normal numbers of monocytes, macrophage, and dendritic cells. In experimental colitis, CD206-deficient mice had attenuated inflammation compared with wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…MRC1 has been suggested to play no role in disease severity of mice infected with various pathogens, including fungi and parasites. 41,42 Also, it has been shown to promote glomerulonephritis 43 in part through augmented Fc-mediated function and to enhance experimental colitis 23 through enhanced miR-511-3p–controlled activation of LPS–Toll-like receptor 4 (TLR4) signaling. Furthermore, Emara et al 4 suggested the importance of MRC1 in recognition of a major cat allergen, Fel d 1, and its subsequent influence on specific antibody response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRC1 has been suggested to play no role in disease severity of mice infected with various pathogens, including fungi and parasites. 41,42 Also, it has been shown to promote glomerulonephritis 43 in part through augmented Fc-mediated function and to enhance experimental colitis 23 through enhanced miR-511-3p–controlled activation of LPS–Toll-like receptor 4 (TLR4) signaling. Furthermore, Emara et al 4 suggested the importance of MRC1 in recognition of a major cat allergen, Fel d 1, and its subsequent influence on specific antibody response.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 More recently, miR-511-3p has been found to control macrophage-mediated microbial responses and enhance intestinal inflammation. 23 …”
mentioning
confidence: 99%
“…Patients with pediatric CD showed enhanced duodenal expression of miR-146 , miR-155 and miR-122 [13,14]. MicroRNAs regulated cytokine production in regulatory T cells of UC patients [15], miR-155 targeted Jarid2 transcripts in Th17 cells in an experimental dextran sulfate sodium (DSS)-induced colitis in mouse [16], and increased miR-511-3p expression in mouse macrophages has been linked to intestinal inflammation [17]. By contrast, miR-31 expression increased while miR-21 , miR-155 and miR-146a levels decreased in colonic CD3 + T cells in UC remission [18].…”
Section: Micrornas In Ibdmentioning
confidence: 99%
“…In fact, this upregulation has led to the MR being used as a marker for alternatively activated macrophages (304). Within the MR gene is a co-regulated microRNA (miR-511-3p), that modulates cellular activation in tumour associated and other macrophages and was recently shown to contribute to intestinal inflammation (305,306). The extracellular domain of the MR can also be cleaved by metalloproteinases following cellular activation, through Dectin-1 signalling for example, releasing a functional soluble form (sMR) (307).…”
Section: The Macrophage Mannose Receptormentioning
confidence: 99%